Social Desirability in Environmental Psychology Research: Three Meta-Analyses - Vesely, Stepan; Klöckner, Christian A. (Frontiers in Psychology, 2020)
That social desirability might be a confounder of people’s survey responses regarding environmental actions has been discussed for a long time. To produce evidence for or against this assumption, we conducted meta-analyses of correlations between social desirability scales and self-reports of environmentally relevant behaviors, intentions and (broadly defined) attitudes, based on data from 29 previously published papers. The pooled correlations with social desirability are generally small, ranging from .06 to .11 (.08 to .13 when correcting for measurement error attenuation). However, our results do not lead to the conclusion that social desirability can be completely disregarded by environmental psychologists as a potential confounder. For example, we found evidence of substantial heterogeneity across studies, so the effect of social desirability may be more pronounced in specific cases. Continued attention to social desirability bias is needed to fully understand its possible subtle effects.